ASSESSING CO-EDUCATION AND CHEMISTRY ATTAINMENT IN THE NORTHERN REGION OF SIERRA LEONE: none (International Journal of Scientific Research and Management (IJSRM), 2021)
This study covered nineteen senior secondary schools in the Northern region of Sierra Leone. The study is aimed at assessing the comparative attainment of pupils in single-sex and co-educational schools. A desk study of secondary data wherein documents and records relating to appropriate data sources were studied to obtain background information on co-education and chemistry attainment. A sample size of eight hundred and fifty seven (857) pupils from nineteen (19) senior secondary schools in the Northern regions of Sierra Leone who sat to the chemistry papers in the WASSCE of 2019. The study revealed that the proportions of credit and above in chemistry for boys and girls in single-sex schools are significantly higher than those of their counterparts in co-educational schools, and that the proportion of bare pass for boys is higher than that of girls, irrespective of whether the pupils are in single-sex or co-educational schools. Girls should do better as well as boys in chemistry if given the opportunity to do it and if provided with adequate motivation.